2022
DOI: 10.1111/dar.13585
|View full text |Cite
|
Sign up to set email alerts
|

Illicit drug use among lesbian, gay, bisexual, pansexual, trans and gender diverse, queer and asexual young people in Australia: Intersections and associated outcomes

Abstract: Introduction High rates of illicit drug use have been reported among gay and bisexual young men, however limited research has examined patterns of drug use among the broader population of lesbian, pansexual, trans and gender diverse, asexual and queer (LGBTQA) young people. We examined factors associated with illicit drug use in the past 6 months and lifetime experiences of self‐reported concern with drug use among LGBTQA youth in Australia. Methods A cross‐sectional survey was conducted involving 6418 LGBTQA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 57 publications
2
17
2
Order By: Relevance
“…The majority of these students reported hearing "negative remarks regarding gender identity or gender expression" at school either "sometimes"/"frequently" (a combined 70%), and less than a third (28%) indicated that they felt safe engaging in any public affection with other GSD students. In keeping with this, almost two thirds of trans young women (64%) and more than half of trans young men (54%) reported missing at least one day of school over the previous 12 months because they felt unsafe (Hill et al, 2021); notably, safety at school sits alongside school-based wellbeing as identified rights of children's/adolescents' access to quality education within Australia's National Quality Framework (Australian Children's Education & Care Quality Authority, 2020).…”
Section: Marginalizing School Climatesmentioning
confidence: 65%
See 3 more Smart Citations
“…The majority of these students reported hearing "negative remarks regarding gender identity or gender expression" at school either "sometimes"/"frequently" (a combined 70%), and less than a third (28%) indicated that they felt safe engaging in any public affection with other GSD students. In keeping with this, almost two thirds of trans young women (64%) and more than half of trans young men (54%) reported missing at least one day of school over the previous 12 months because they felt unsafe (Hill et al, 2021); notably, safety at school sits alongside school-based wellbeing as identified rights of children's/adolescents' access to quality education within Australia's National Quality Framework (Australian Children's Education & Care Quality Authority, 2020).…”
Section: Marginalizing School Climatesmentioning
confidence: 65%
“…Research from the Australian context likewise reveals unique institutional microaggressions and points to associated outcomes for TGD students. In a recent survey of more than 6,400 GSD young people aged 14-21 years, TGD participants were much less likely to report feeling safe at their educational institutions, compared with the participating cisgender, sexuality diverse cohort (Hill et al, 2021). Looking specifically at the cohort of participating secondary school students, just over a third (34%) indicated that none of the survey's four articulated options for gender affirmationsuch as using their chosen name or pronouns, using bathrooms, using changing rooms, or wearing the school uniform aligned with their gender identity-were available to them at their school.…”
Section: Marginalizing School Climatesmentioning
confidence: 97%
See 2 more Smart Citations
“…Many gender and sexuality diverse young people (including those identifying as lesbian, gay, bisexual, transgender, nonbinary, queer, questioning, asexual, agender, or who have otherwise diverse gender and/or sexuality experiences; henceforth respectfully referred to using the umbrella term, LGBTQ+) live happy, fulfilled lives. Yet higher rates of mental ill‐health among LGBTQ+ young people in the United States, Canada, and the United Kingdom have been consistently reported in the literature (Hill et al, 2021; Lin et al, 2021; Meyer et al, 2021). By contrast, there has been significantly less work conducted in Australia, where gender and sexuality indicators are often excluded in population‐level data sets.…”
Section: Introductionmentioning
confidence: 87%